2022
DOI: 10.3390/polym14101980
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Composite Nanofiltration Membranes for Arsenic Removal

Abstract: In recent years, significant attention has been paid towards the study and application of mixed matrix nanofibrous membranes for water treatment. The focus of this study is to develop and characterize functional polysulfone (PSf)-based composite nanofiltration (NF) membranes comprising two different oxides, such as graphene oxide (GO) and zinc oxide (ZnO) for arsenic removal from water. PSf/GO- and PSf/ZnO-mixed matrix NF membranes were fabricated using the electrospinning technique, and subsequently examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…A possible foulant layer might be porous as well. Membranes are mesoporous and have pore sizes ranging from 0 to 100 nm [ 29 ]. Thus, the fouling-induced changes in the micropore region (<2 nm), mesopore region (2–50 nm), and macropore region (≥50 nm) were of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible foulant layer might be porous as well. Membranes are mesoporous and have pore sizes ranging from 0 to 100 nm [ 29 ]. Thus, the fouling-induced changes in the micropore region (<2 nm), mesopore region (2–50 nm), and macropore region (≥50 nm) were of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Three electrospun nanofibrous mixed-matrix membranes were used for this study, as reported earlier [ 29 ]. The membranes were P, CP, and MCP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed matrix membranes (MMMs) are membranes in which NPs are embedded as a dispersed phase into a polymer matrix, which can be achieved using techniques such as PI, electrospinning, crosslinking, LBL deposition, etc. [ 77 , 78 , 79 , 80 , 81 , 82 ]. This review will mostly focus on nanomaterials incorporated in the polymer substrate, but a few examples of other possibilities shall be discussed as well.…”
Section: Introductionmentioning
confidence: 99%